Pengembangan Video Animasi IPS dengan Aplikasi Doratoon pada Materi Perdagangan Antardaerah dan Antarnegara - Sidabutar, Marta Juliati; Lestari, Natalia Ayu (Universitas Negeri Padang, 2024)
Based on the results of field observations, the problem was found to be the absence of interactive learning media applied with teachers in the learning process. The aim of this research is to develop learning media in the form of animated videos based on doratoon learning on the trading materials between regions and countries. This research uses the type of development research (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This research was conducted at MTs Negeri 4 Mandailing Natal, with a population in class VIII. The instrument used in the research were feasibility and practicality questionnaire. Descriptive statistics were used for data analysis.The results of this research, based on assessments carried out by validation experts and user responses, obtained an average assessment percentage of 89.43% in the